The Early Middle Ages of Samuel Beckett. Issue 1 (April 2016) - Byron, Mark
Abstract : Beckett's investigations in the history of philosophy are well represented in his notebooks of the late 1920s and early 1930s, which provide a close record of his reading in ancient, medieval, and modern philosophy, as well as in history, literature, and psychology. Numerous scholars – Daniella Caselli, Anthony Uhlmann, Dirk Van Hulle, Matthew Feldman, and David Addyman among others – have carefully delineated the relationship between Beckett's note-taking and his deployment of philosophical sources in his literary texts. Whilst the focus quite rightly tends to fall on Beckett's absorption of Presocratic, Aristotelian, Cartesian, and post-Cartesian philosophy, there are important strands of early medieval philosophy that find expression in his literary work. The philosophy notes housed in the library of Trinity College, Dublin, provide insights into Beckett's reading in medieval philosophy, drawing almost exclusively from Wilhelm Windelband's History of Philosophy . The epoch spanning from Augustine to Abelard saw central concepts in theology and metaphysics develop in sophistication, such as matters of divine identity and non-identity, the metaphysics of light, and the nature of sin. The influence of the Eastern Church Fathers (Gregory of Nyssa, Basil of Caesarea, Maximus the Confessor) on Western metaphysics finds expression in the figuration of light and its relation to knowing and unknowing. This eastern theological inflection is evident in the 'Dream' Notebook, where Beckett's notes demonstrate his careful reading of William Inge's Christian Mysticism . These influences are expressed most prominently in various themes and allusions in his early novels Dream of Fair to Middling Women, Murphy, and Watt . The formal experiments and narrative self-consciousness of these early novels also respond to the early medieval transformation of textual form, where the precarious post-classical fruits of learning were preserved in new modes of encyclopaedism, commentary, and annotation. Beckett's overt display of learning in his early novels was arguably a kind of intellectual and textual preservation. But the contest of ideas in his work subsequently became less one of intellectual history and more that of immanent thinking in the process of composition itself.